Mathematical model system of course mode of exact horyzontuvannya - Сущенко, О.А. (Proceedings of National Aviation University (archive), 2006)
The mathematical description of course determination system in the mode of levelling is created. Angle motion of the base on which the sensors are mounted is taken into consideration. To provide the choice of the sampling interval the mathematical description is complemented by the models of service electronics.